HYDROLYSIS OF PLANT BIOMASS USING RECOMBINANT ALPHA-AMYLASE FROM BACILLUS LICHENIFORMIS AND XYLANASE FROM BACILLUS SONORENSIS - Kiribayeva, A.; Silayev, D.; Abdullayeva, A.; Shamsiyeva, Yu.; Ramankulov, Ye.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2022)
With the reduction of fossil hydrocarbon sources and the increasing need for energy, chemical resources and food, the use of biomass as a renewable source is of great importance. This, in turn, necessitates efficient enzymes for bioconversion of biomass. Enzymes are important in industry because they are biocatalysts for complex chemical processes. The conversion of plant biomass into sugars requires a complex of enzymes whose composition must be adapted to the type of biomass and а pretreatment method. The efficiency of enzymatic hydrolysis can be increased by optimizing the composition of the enzymatic complex, increasing the catalytic activity and stability of the enzymes included in it. A large number of microbial amylases are now commercially available, and they have almost completely replaced chemical starch hydrolysis in the processing industry. The use of bacterial xylanases is a key step in the conversion of lignocellulosic polysaccharides into fermentable sugars for the production of biofuels and value-added products. Enzyme complexes containing both α-amylases and xylanases have found applications in the pulp and paper industry and feed production. Recombinant α-amylase and xylanase from Bacillus licheniformis and Bacillus sonorensis, respectively, were obtained using recombinant DNA technology. These enzymes were purified by metal affinity chromatography from the lysate of induced cultures of recombinant strains. Enzymatic hydrolysis of potato starch and birch xylan with these recombinant enzymes was performed. The hydrolysis products of these polysaccharides were studied by thin-layer chromatography. It was found that the products of hydrolysis of potato starch using recombinant α-amylase were maltose and maltooligosaccharides and a small amount of glucose. Xylan was isolated from birch sawdust and hydrolyzed by recombinant xylanase. Detection of the hydrolysis products of xylan showed that xylan is hydrolyzed to oligoxylans with a degree of polymerization of at least 2 monomers. No xylose was detected among the hydrolysis products. The results indicate that α-amylase from Bacillus licheniformis and xylanase from Bacillus sonorensis are endoenzymes.